The impact of utilising active learning methods towards ecm366 course outcome / Normadiana Mohammad Hanapi … [et al.] - Mohammad Hanapi, Normadiana; Omar, Norizah; Samat, Mohammad Mokhtar; Mohd Kamal, Mohd Mawardi (Universiti Teknologi MARA Cawangan Pahang, 2020)
Active learning can be defined as a form of learning in which educator strives to involve students in the learning process more directly than in conventional methods. One of the active learning methods is jigsaw classroom. This method require the students to work in smaller interdependent groups, each student is given a part of a topic to be studied and when finished, the students fit their pieces of the subject area together to form a complete jigsaw picture. This study was carried out to identify the effectiveness of implementations of the jigsaw classroom techniques in the theoretical subjects and to compare the student achievement in terms of course outcome by applying jigsaw classroom technique. Depth knowledge of theoretical construction management subject such as types of contract in Malaysia construction industry is important for examination reasoning, problem solving and improvement in technical skills. As a result, 98% students had given response for the advantages of JCL of Teaching-Learning and the common advantages perceived that Jigsaw Classroom Learning can improve their communication skills. However, the general trend of students and faculty towards this subject is; it is dry, volatile and difficult to learn. The reasons could be due to vastness of the subject, effectiveness of student learning, period of study more than one hour/period, physical environment within the classrooms (one-way teaching by instructor) and so on. Student concentration will drop as low as possible in the classes while using one way teaching. Therefore using jigsaw classroom as a cooperative learning technique can develop the teachings-learning to be more efficient of the students and also improve student’s academic performance